2022
DOI: 10.9734/ijpss/2022/v34i1330974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Productivity of some Barely Genotypes under Deficient Water Application in Clayey Soils

Abstract: This study is intended to identify barely genotypes efficient for water use. For this, a field experiment was conducted at Sakha Research Station. The experimental design was randomize complete block with three replicates during 2018/2019 and 2019/2020 growing seasons. Twenty barely genotypes were grown under two water application treatments ((full irrigation (FI) and water stress (WS)). The values of applied irrigation water were 3430 and 1995 m3/ha under WS and FI, respectively, being lower by 42%, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
5
2
0
Order By: Relevance
“…The highest values in the second season may be a result of the lowest temperature and higher relative humidity than in the first one. Similar results were obtained by [5,24]. Results showed that, water deficit reduced all studied traits.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The highest values in the second season may be a result of the lowest temperature and higher relative humidity than in the first one. Similar results were obtained by [5,24]. Results showed that, water deficit reduced all studied traits.…”
Section: Discussionsupporting
confidence: 88%
“…Results showed that, water deficit reduced all studied traits. These results were confirmed by [20,25,26,5]. The reduction in number of grains/spike may be due to premature abortion of florets [27].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The 2-year average WCU values were 1332, 1250, and 1208 m 3 /fed for I I 1 , I 2 , and I 3 irrigation treatments, respectively. Results agree with [18]. 3 consumed water) and WP (0.81 kg grain/m 3 applied water) were recorded for Giza 129 genotype.…”
Section: Irrigation Parameterssupporting
confidence: 89%